THE ESSENCE OF HUMAN CAPITAL (British Journal of Global Ecology and Sustainable Development, 2022)
The article examines the competition between countries and socio-economic systems in the global technology market has become in itself a 5-step forward, competition for the creation of high-quality and valuable human capital. Because, ultimately, it is argued that any economic, scientific, technological and similar miracles and "leaps" can be carried out only with the participation and assistance of an army of educated, erudite, inquisitive, enterprising and selfless people – innovative human capital.